2021
DOI: 10.3389/fsurg.2021.683041
|View full text |Cite
|
Sign up to set email alerts
|

Selective Parathyroid Autotransplantation During Total Thyroidectomy for Papillary Thyroid Carcinoma: A Cohort Study

Abstract: Purpose: The relationship between the selective parathyroid gland (PG) autotransplantation and hypoparathyroidism is still not completely clear. The aim was to ascertain whether the number of autotransplanted PGs affected the incidence of hypoparathyroidism and recovery of parathyroid function in the long-term for patients with papillary thyroid carcinoma (PTC).Methods: A retrospective cohort study included all patients with PTC who had underwent primary total thyroidectomy with central neck dissection between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Selective parathyroid autotransplantation during endoscopic radical resection of thyroid carcinoma is effective in preventing permanent hypoparathyroidism. This is consistent with the findings of Qiu’s ( 31 ) study. At the same time, we found that the diameters of thyroid cancer nodules was not associated with the occurrence of transient hypoparathyroidism or permanent hypoparathyroidism which was the same conclusion as Yazıcıoğlu et al ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Selective parathyroid autotransplantation during endoscopic radical resection of thyroid carcinoma is effective in preventing permanent hypoparathyroidism. This is consistent with the findings of Qiu’s ( 31 ) study. At the same time, we found that the diameters of thyroid cancer nodules was not associated with the occurrence of transient hypoparathyroidism or permanent hypoparathyroidism which was the same conclusion as Yazıcıoğlu et al ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Qiu et al. ( 31 ) concluded that parathyroid autotransplantation is an independent risk factor for transient hypoparathyroidism but a preventive factor for permanent hypoparathyroidism and recommended selective parathyroid autotransplantation. Su et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the magnified view in endoscopy offered us the chance to distinguish and preserved the vessels of the PTGs [ 21 ]. Some of the studies have shown that if the PTGs cannot be preserved in situ , autotransplantation is recommended for suspicious PTGs confirmed by an intraoperative frozen section and this procedure will not increase the complication rates of permanent hypocalcemia [ 22 , 23 ]. The major and minor complication rates were not higher than those in other reports [ 19 ], indicating the safety and feasibility of the modified approach.…”
Section: Discussionmentioning
confidence: 99%
“…Its sensitivity and specificity reached 100% and 80.4% respectively, while the latter reached 94.7% and 84.8% respectively. The decrease of iPTH can be regarded as an important technical index reflecting the damage of PTF during surgery, which can effectively predict early postoperative hypocalcemia and is closely related to persistent HPT (20). However, whether perioperative vitamin D deficiency increases the risk of postoperative PTF reduction remains controversial.…”
Section: Effects Of Ptf On Serum Phosphorus Levelmentioning
confidence: 99%